2019
DOI: 10.1016/j.jecp.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering in children: Examining task-unrelated thoughts in computerized tasks and a classroom lesson, and the association with different executive functions

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
3
27
3
1
Order By: Relevance
“…68 ). As certain subtypes of spontaneous cognitive processes are detectable in time-varying functional connectivity measurements 68 , it could be hypothesized that part of our results might pertain to the age-related changes in the occurrence of mind wandering episodes and in the content/type of spontaneous cognitive processes observed from childhood to young adulthood and from young to late adulthood 63,[69][70][71][72][73][74][75][76][77] . Further studies should investigate this critical issue.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 95%
“…68 ). As certain subtypes of spontaneous cognitive processes are detectable in time-varying functional connectivity measurements 68 , it could be hypothesized that part of our results might pertain to the age-related changes in the occurrence of mind wandering episodes and in the content/type of spontaneous cognitive processes observed from childhood to young adulthood and from young to late adulthood 63,[69][70][71][72][73][74][75][76][77] . Further studies should investigate this critical issue.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 95%
“…Although there is a growing literature on MW in adults, there are few studies of MW during childhood and only one on childhood ADHD. The few studies in typically developing children showed that children aged 8–12 years were able to report MW in a valid way (Keulers & Jonkman, ; Mrazek et al , ; Ye, Song, Zhang, & Wang, ). In these studies, elevated MW was related to measures of lower executive control, poor reading comprehension and reduced well‐being (Keulers & Jonkman, ; Mrazek et al , ; Ye et al , ).…”
mentioning
confidence: 99%
“…The few studies in typically developing children showed that children aged 8–12 years were able to report MW in a valid way (Keulers & Jonkman, ; Mrazek et al , ; Ye, Song, Zhang, & Wang, ). In these studies, elevated MW was related to measures of lower executive control, poor reading comprehension and reduced well‐being (Keulers & Jonkman, ; Mrazek et al , ; Ye et al , ). In the only previous study on MW in children with ADHD, MW was found to be elevated during task performance in medicated children, whilst mind blanking was elevated in un‐medicated children with ADHD (Van den Driessche et al , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These same ideas could be used to examine individual differences in cognitive development; that is, some developmental variation could be due to variation in intensity (Chevalier, 2018), and other developmental variation could be due to variation in consistency (Keulers & Jonkman, 2019), in addition to differences in types of control. For example, some children could perform poorly on an attention-control task because they have specific deficits in the type of control engaged (e.g., conflict resolution).…”
Section: Discussionmentioning
confidence: 99%